Penggunaan Value Added Intellectual Capital (VAIC) Sebagai Prediktor Nilai dan Kinerja Keuangan Perusahaan (Studi Empiris Pada Perusahaan di Sektor Miscellaneous, Consumer Goods Property, Real Estate & Building Construction dan Infrastructure, Utilities - Firman Adnan; Josephine Sudiman (The Indonesia Capital Market Institute, 2019)
This research is motivated by the development of science and technology that causes many companies to make business strategies based on science, namely intellectual capital (IC). One measurement that can be used to measure IC is VAICTM developed by Pulic (2000). The purpose of this study is to analyze the effect of intellectual capital on the market value and financial performance of companies. The research method used is a simple linear regression method. The sample of this study are companies of the miscellaneous, consumer goods, property and infrastructure sectors listed on the Indonesia Stock Exchange between 2015 and 2018. The results of this study indicate that IC is only able to be a predictor of financial performance as measured by using return on assets (ROA) and return on equity (ROE), while IC is not able to be a predictor of company value measured using price book value (PBV), price earnings ratio (PER) and Tobin's Q (Q).